A very rare case of mycobacterium gordonae infection of the breast. Issue 11 (26th October 2020) - Pamparino, Silvia; Valente, Irene; Tagliafico, Alberto; Dentone, Chiara; Bassetti, Matteo; Mennella, Simone; Calabrese, Massimo; Garlaschi, Alessandro
Abstract: Mastitis is a common disease in women with both infectious and noninfectious causes. Most cases occur during lactation and are caused by Staphylococcus aureus and Streptococcus species; parasites and Mycobacteria have rarely been reported to cause breast infections (Mandell, Douglas, and Bennett's principles and practice of infectious diseases (9th edn);2019, Am J Respir Crit Care Med. 2007;175:367). Nontuberculous mycobacteria (NTM) which are also referred to as atypical mycobacteria, mycobacteria other than tuberculosis (MOTT), or environmental mycobacteria are a large group of Mycobacteria which are becoming increasingly common cause of infection all over the world (Arch Dermatol. 2006;142:1287). NTM can cause infection diseases especially in immunocompromised patients, such as HIV‐positive hosts, most commonly in the lungs, skin and soft tissue, lymph nodes or rarely spread with multiorgan dissemination (Arch Plast Surg. 2014;41:759). Mycobacterium gordonae (M. gordonae) is a slow‐growing atypical mycobacterium that is considered the least pathogenic NTM. The organism is ubiquitous, and mostly isolated from soil and water. Despite its nonvirulent nature, clinically significant infections have been reported also in some immunocompetent patients (J Formosan Med Assoc. 2020, Clin Infect Dis. 1992;1229). We report the first documented case of breast infection in a young immunocompetent woman sustained by Mycobacterium Gordonae.